2021
DOI: 10.1177/16878140211026720
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ANN model for prediction of tool wear in turning EN9 and EN24 steel alloy

Abstract: An imperative requirement of a modern machining system is to detect tool wear while machining to maintain the surface quality of the product. Vibration signatures emanating during machining with a single point cutting tool have proven to be good indicators for the tool’s health. The current research undertaken utilizes vibration signatures while turning EN9 and EN24 steel alloy to predict tool life using Artificial Neural Network (ANN). During initial meager experimentation, tool acceleration during machining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The idea behind ANNs is to emulate the brain's functioning to solve technical problems that may not be solvable using other methods, as noted by Svorcan et al [36]. Thus, ANN serves as a decision support tool [37]. The use of ANNs has reduced the development time and enhanced the flexibility of the studied system [38].…”
Section: Ann-based Modelingmentioning
confidence: 99%
“…The idea behind ANNs is to emulate the brain's functioning to solve technical problems that may not be solvable using other methods, as noted by Svorcan et al [36]. Thus, ANN serves as a decision support tool [37]. The use of ANNs has reduced the development time and enhanced the flexibility of the studied system [38].…”
Section: Ann-based Modelingmentioning
confidence: 99%
“…The feed rate was shown to be the most important component based on the findings. According to Baig et al [33], to preserve the product's surface finish during milling, a modern machining system needs to be able to recognize tool wear. It has been demonstrated that the vibration fingerprints generated by a single-point milling cutter during machining are reliable indicators of the tool's condition.…”
Section: Ann-ga On Prediction Of Tool Wearmentioning
confidence: 99%
“…It is therefore necessary to replace the tool regularly, in order to optimize production and reduce costs [ 3 ]. It is estimated that tool costs can account for up to 12% of the production costs of a part [ 4 ]. Thus, to ensure that tools operate under nominal conditions and to minimize tool costs, the monitoring of cutting tools has become an important research topic [ 5 ].…”
Section: Introductionmentioning
confidence: 99%